Association between patient-reported functional measures and incident falls - Wanfen Yip; Lixia Ge; Bee Hoon Heng; Woan Shin Tan (Scientific Reports, 2021)
Abstract Lower extremity muscle strength, and functional limitations are important modifiable predictors of falls, but are often examined using performance based measures. We examined the association between self-reported physical function limitations, determined using Late-Life Function and Disability Instrument(LLFDI) and incident falls in community-dwelling elderly individuals. 283 older adults participants were included in this analysis. Physical function limitations were defined as a person’s difficulty in completing items of the lower extremity function domain and composite scores of the LLFDI. Information on falls was obtained through a standardised questionnaire. At one-year follow-up, 15.2% (43) of the participants experienced their first fall. In the multivariable analysis, individuals who reported difficulties in items of lower extremity function domain were more likely to experience a fall (incidence rate ratio[IRR]: ranging between 2.43 and 7.01; all P ≤ 0.046). In addition, decreasing advanced lower extremity function scores (IRR: 1.70, 95% confidence interval[CI]): 1.04, 2.78) and overall function component score (IRR: 2.05, 95% CI: 1.22, 3.44) were associated with higher risk of incident falls. Physical function limitations, determined using LLFDI, were associated with incident falls. Our findings provide further evidence that the LLFDI function component has the potential to be used as a self-assessment tool for fall risk.